Thailand: healthcare delivery system - David Hughes (The Wiley-Blackwell Encyclopedia of Health, Illness, Behavior, and Society, 2nd edition, due 2023.)
This encyclopedia entry reviews the Thai system, and particularly the development of universal healthcare coverage from its introduction in 2002 to the present.